FMRI of shared-stream priming of lexical identification by object semantics along the ventral visual processing stream. (October 2019) - Neudorf, Josh; Ekstrand, Chelsea; Kress, Shaylyn; Borowsky, Ron
Abstract: Distributed sub-systems of the brain's semantic network have been shown to process semantics associated with visual features of objects (e.g., shape, colour) in the ventral visual processing stream, whereas semantics associated with actions are processed in the dorsal stream. Orthographic lexical processing has also been shown to occur in the ventral stream. Past research from our lab (Neudorf et al., 2019) has demonstrated a temporal (i.e., reaction time) priming advantage for object primes over action primes in the lexical decision task consistent with ventral shared-stream processing of visual feature object semantics and orthographic lexical identification, whereby object primes produced larger priming effects than action primes. The current experiment explored this paradigm using functional magnetic resonance imaging (fMRI) and identified the potential loci of shared-stream processing to regions in the ventral stream just anterior to colour sensitive visual area V4 cortex in the left fusiform gyrus and anterior to lexical and shape sensitive regions in the left fusiform gyrus, as well as in cerebellar lobule VI. Action priming showed more activation than object priming in dorsal stream motion related regions of the right parietal occipital junction, right superior occipital gyrus, and bilateral visual area V3. The fMRI activation observed in this experiment supports the theory that spatially shared-stream activation occurs in the ventral stream during object (but not action) priming of lexical identification, which is consistent with our earlier behavioural research showing that these processes are also temporally shared. Highlights: FMRI of shared-stream lexical and object semantic processing in the ventral stream. Object priming of lexical processing anterior to both V4 (colour) and VWFA (shape). Cerebellar lobule VI may act as an additional object semantic sub-system.